Liberalization of Trade With The EU and Its Impact on The Reduction in CEFTA 2006 Trade Balance Deficit - Kurtovic, Safet; Talovic, Sead (International Journal of Economics and Financial Issues, 2015)
This paper’s main objective is to research the effect of liberalization of trade with the European Union (EU) and its impact on the reduction in trade balance deficit of CEFTA 2006 (Central European Free Trade Agreement). It utilizes panel data time-series in the interval from 2007 to 2013. It applies economical gravity model and econometric dynamic panel data techniques: panel data models (PD), fixed effects models (FE) and random effects models (RE). It has been concluded that trade liberalization positively impacts the reduction in trade balance deficit of CEFTA 2006 countries, i.e. that export and import between the exporting country and the importing country within time period , gross domestic product of the country , gross domestic product per capita of the country within time period , distance between the country and country , dummy variables (free trade agreements and sharing a common border) are statistically significant. Additionally, it has been determined that FE is more favorable than RE when it comes to achieving better assessment of the effects of independent variables on a dependent variable. Keywords: Liberalization; trade balance; deficit; integration; export; import JEL Classifications: F1; F15